Kisspeptin leads to calcium signaling in cultured rat dorsal root ganglion neurons - Kelestimur, Haluk; Bulut, Ferah; Canpolat, Sinan; Ozcan, Mete; Ayar, Ahmet (Aepress Sro, 2021)
Although kisspeptin and GPR54 have been reported to be expressed in the neurons of the dorsal root ganglion (DRG) of rats, and kisspeptin has been suggested to be involved in pain modulation in rodents, there is no study on the effects and mechanisms of kisspeptin on sensory neurons. Therefore, the aim of this study was to investigate the effects and mechanism of kisspeptin on intracellular free calcium levels in cultured rat DRG neurons. Bath application of kisspeptin-10 increased intracellular free calcium levels ([Ca2+](i)). In the absence of extracellular calcium, the kisspeptin induced an attenuated but still significant increase in [Ca2+](i). [Ca2+](i) responses persisted in the presence of protein kinase C (PKC) inhibitor. Data from this study revealed that kisspeptin-10 activates [Ca2+](i) signaling independent of PKC in cultured rat sensory neurons suggesting that peripheral site is also involved in the pain modulating effect of kisspeptin.
Keywords: Kisspeptin; Sensory neurons; Calcium signaling; Protein kinase C